ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS DENGAN PENDEKATAN ALTMAN Z-SCORE PADA PERUSAHAAN CONSUMER NON-CYCLICAL YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Putri Lestari; Imronudin (JURNAL LENTERA BISNIS, 2024)
This study aims to analyze the factors that influence financial distress with the Altman Z-score approach in non-cyclical consumer companies listed on the IDX in 2020-2023. This research is included in quantitative research. The population in this study uses companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX). Sampling using probability random sampling. The data source used is secondary data. Data collection techniques through reading and analyzing various literature books, journals, and also theses. As well as the use of the website through the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id and the official website owned by the Company. The data analysis technique uses data processing assistance through excel 2019 software and Eviews or Econometric Views version 12 with the regression analysis method. The results of the study are that profitability and total asset turnover have a positive and significant effect on financial distress. Leverage has a negative and significant effect on financial distress. However, simultaneously the independent variables in this study, namely profitability, leverage, and total assets turnover, have an overall influence on financial distress.